Analysis of the profile of basic mathematical skills and misconceptions of prospective elementary school teachers - Lintang Analisa Ekasari; Fery Muhamad Firdaus; Syarifah Anjani Pawestri (Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2025)
This study aims to analyze the profile of basic mathematical skills and misconceptions of prospective elementary school teachers (PGSD students) and to describe the relationship between these two constructs. Using a descriptive quantitative approach, data were collected from 282 PGSD students from five state universities through a basic mathematics ability test, an error analysis sheet, and a misconception classification rubric that had been validated by experts and tested for reliability. Descriptive statistics were applied to map students’ abilities across five domains (numbers and operations, algebra, geometry, measurement, and data analysis/probability), while qualitative error analysis was employed to identify conceptual, procedural, misinterpretation, and careless errors as indicators of misconceptions. The findings show that students’ basic mathematical skills are generally in the moderate category, with the highest mean score in geometry and the lowest in algebra, and that conceptual errors (44.1%) are the most dominant, especially in numbers and operations and algebra. The analysis further reveals a clear pattern that lower levels of basic mathematical skills are associated with higher levels of misconception, indicating that misconceptions are rooted in weak conceptual understanding rather than mere carelessness. This study contributes to the field of education by offering an integrated empirical profile of basic skills and misconceptions among prospective elementary school teachers as a basis for developing diagnostic assessments and strengthening PGSD curricula that emphasize conceptual understanding in basic mathematics learning.